Equipment to measure the oxygen diffusion rate and redox potential in soil - Herrmann, Paulo Sergio de Paula; Andrade, Manoel Gomes de; Colnago, Luiz Alberto; Silveira, Pedro Marques da (Pesquisa Agropecuaria Brasileira, 1997)
An instrument to measure the oxygen diffusion rate (ODR) and redox potential (RP) to characterize soil aeration with the same electrodes was developed and tested. The analogic circuits were based on BiMOS operational amplifiers, and the digital, on CMOS technology. The system has six platinium electrodes, 0.35 mm in diameter for measurements, and one calomel electrode for reference. The ODR or redox function is selected by a switch, and the electrode selection is made by a thumbwhell switch. The data are shown in a 3 1/2 liquid cristal display. The redox potential can be measured from -1.999 V to + 1.999 V, and the ODR, from -19.99 μA to + 19.99 μA. The results were similar to those obtained with the redox and ODR commercial equipments.
Keywords: oxygen diffusion rate; redox potential; soil aeration